A constructive heuristic algorithm for multi-stage transmission expansion planning under N-1 security constraints - Khorasani, Hamid [UNESP]; Romero, Rubén [UNESP] (Praise Worthy Prize, 2015)
The transmission expansion planning (TEP) problem in modern power systems is a large-scale, mixed-integer, non-linear, and non-convex problem. The problem becomes even more complicated when the security constraints are taken into account as in some large-scale systems, finding the optimal solution is inaccessible. This paper presents a novel mathematical model to solve the security constraints of transmission system expansion planning problem via a constructive heuristic algorithm (CHA). The proposed CHA is extended to multi-stage planning. The basic idea comes from Garver’s work applied to the transportation model. Nevertheless, the proposed algorithm works with a hybrid linear model. The proposed CHA finds an acceptable solution in an iterative process, where in each step, a circuit is chosen by using a sensitivity index and is subsequently added to the system. Moreover, several simulation studies and tests were carried out on Garver, the South Brazilian system, and the North Brazilian system, to demonstrate the effectiveness of the proposed methodology.
Keywords: Constructive Heuristic Algorithm; Mixed-Integer Non-Linear Programming; Multistage Transmission Expansion Planning; N-1 Security